Pengaruh Kadar Glukosa Darah Terhadap Fungsi Kognitif Pada Penderita Diabetes Melitus Tipe 2 Di Grha Diabetika Surakarta - Putri Widyandhini, Nariswari, dr. Nur Hidayat, Sp. PD, dr. Erika Diana Risanti (2015)
Background: Diabetes mellitus is a chronic diseases that can cause variety of complications. By 2013 the number of sufferers of Diabetes mellitus type 2 reached 382 million people mostly in countries with low and medium income earners. State of hyperglycemia in patients DM can accelerate the decline in cognitive function through mechanisms of oxidative stress or the formation of free radicals. Objectives: This research aims to analyze the influence of blood glucose levels with cognitive function in people with type 2 Diabetes mellitus in GRHA Diabetika Surakarta. Methods: this research is a study of the correlation by using analytic approach of cross sectional. The number of respondents to the research as much as 30 samples of type 2 DM patients in GRHA Diabetika Surakarta selected with the purposive sampling. This research was conducted by way of a record score of cognitive functioning questionnaires sufferers with MMSE (Mini Mental State Examination). As well as taking data from patient medical colleagues about blood sugar levels fasting and blood sugar 2 hour post prandial. The data are then tested with the test correlation of Pearson. Results: there is significant correlation between fasting blood glucose levels with cognitive function with a value of r-0,479 and p = 0.007 (p < 0.05). There is also a link between blood glucose levels 2 hour post prandial against cognitive function with a value of r-0,775 and p = 0.000 (p < 0.05). Conclusion: there is the influence of blood glucose levels and cognitive function in patients with type 2 DM in GRHA Diabetika Surakarta